All Days 1998
DOI: 10.2118/49319-ms
|View full text |Cite
|
Sign up to set email alerts
|

Wettability Change Related to the Adsorption of Organic Acids on Calcite: Experimental and Ab Initio Computational Studies

Abstract: We have investigated the interactions between organic acids and a calcite powder by adsorption from an organic phase (benzoic acid and lauric acid in toluene) and from an aqueous phase (benzoic acid and lauric sodium salt. In addition to the experimental study, ab initio quantum chemistry calculations were performed for cluster models, simulating the interactions of molecules with calcite surface sites. At the toluene/calcite interface, acids chemisorb on surface calcium ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…The adsorption layer is formed by orientation of carboxyl groups toward calcite surface because the surface carries positive charges. [23] For engineering purposes, the adsorption isotherms are also plotted as adsorption amount (mg of NA per g calcite powder) versus total acid number (TAN) and are shown in Figure 3. TANs were calculated by amount (in mg) of KOH required to neutralize NA in 1 mL of the oil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption layer is formed by orientation of carboxyl groups toward calcite surface because the surface carries positive charges. [23] For engineering purposes, the adsorption isotherms are also plotted as adsorption amount (mg of NA per g calcite powder) versus total acid number (TAN) and are shown in Figure 3. TANs were calculated by amount (in mg) of KOH required to neutralize NA in 1 mL of the oil.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental body of this work is given in detail in a SPE paper (SPE 99612) that was presented at the SPE/DOE Symposium of Improved Oil Recovery at Tulsa, Oklahoma April [22][23][24]2006. This paper has been submitted to SPE for peer review, and has been accepted for publication pending a review of the revisions recently provided by the authors.…”
Section: Study Of Weting Behavior and Surfactant Eor In Carbonates Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically the neutral to oil-wet character of carbonate reservoirs may be related to the adsorption of carboxylate molecules diffusing from crude oil to positive sites of the calcite surface [41]. In other words, the wettability of hydrocarbon reservoirs depends on the specific interactions in the oil/rock/brine systems.…”
Section: Brine Composition Andmentioning
confidence: 99%
“…Hansen [9] suggested that strong adsorption of stearic acid on the calcite surface converts the calcite surface to strongly oil-wet. Legens [41] investigated the adsorption difference of benzoic and lauric acids on calcite surface from toluene and water.…”
Section: Role Of Carboxylic Acidsmentioning
confidence: 99%